Assessment of the cost reduction potential of a novel loop-heat-pipe solar photovoltaic/thermal system by employing the distributed parameter model. (1st January 2020) - Ren, Xiao; Yu, Min; Zhao, Xudong; Li, Jing; Zheng, Siming; Chen, Fucheng; Wang, Zhangyuan; Zhou, Jinzhi; Pei, Gang; Ji, Jie
Abstract: A novel micro-channel loop-heat-pipe solar photovoltaic/thermal (LHP- PV/T) system is developed employing the co-axial tubular heat exchanger as the condenser and upper-end liquid header with tiny holes as the liquid feeder. The design facilitates an easier connection among the solar modules. It creates the improved condensation and separate evaporation effects within the LHP. A reduced evaporator area will thereby have a minor impact on the overall heat transfer performance, leading to significant potential for cost reduction. A distributed parameter model is established and validated by experimental data. The model is then applied to analyse the cost reduction potential of the LHP- PV/T via the optimization of geometrical and structural parameters. The impact of the area reduction on the LHP evaporator differs from that on the traditional integral heat pipe PV/T. The decrements in thermal and electrical efficiencies of the LHP- PV/T are 2.47% and 0.03% respectively when the width of heat pipes in the evaporator decreases from 26 to 10 mm. When the number of heat pipes decreases from 30 to 6, the decrements in thermal and electrical efficiencies are 4.63% and 0.12%, whilst the overall system cost drops by 28.58%, thus the cost-effectiveness of the system can be improved. Highlights: . A novel loop heat pipe solar photovoltaic/thermal system is built. . An accurate distributed parameter model is developed. . Cost reduction potential of the system is investigated. . Influences of a reduced evaporator area on LHP differ from those on IHP. . The system cost is reduced by 28.58% with a minor decrement in the performance.